2015
DOI: 10.11603/mcch.2410-681x.2015.v17.i4.5681
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of changes in lipid metabolism indices in organs and tissues of experimental animals under adrenaline stress

Abstract: <p>Diseases of human population, especially in the countries with high level of urbanization, are more often associated now with the influence of different stresses, including emotional one, which is accompanied by adrenaline release.<br />It has been investigated the effect of adrenaline on triacylglycerol (TA G) and cholesterol (CL ) content in different tissues of Wistar rats. It has been determined that under short-term adrenaline load (single injection of adrenaline<br />followed by samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…On the other hand, the utilization of excessive amounts of adrenaline leads to the formation of adrenochrome (a product of the oxidation of adrenaline by free radicals) and free radicals (semiquinone, etc.) with the further intensification of oxidative damage to molecules (Gupta et al, 2014;Shkurashivska & Erstenyuk, 2015;Rabasa & Dickson, 2016). Our experiments have shown that free radical processes on the one hand, and antioxidant protective mechanisms in the body of animals on the other, under normal conditions and, especially under stress, have tissue specificity.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…On the other hand, the utilization of excessive amounts of adrenaline leads to the formation of adrenochrome (a product of the oxidation of adrenaline by free radicals) and free radicals (semiquinone, etc.) with the further intensification of oxidative damage to molecules (Gupta et al, 2014;Shkurashivska & Erstenyuk, 2015;Rabasa & Dickson, 2016). Our experiments have shown that free radical processes on the one hand, and antioxidant protective mechanisms in the body of animals on the other, under normal conditions and, especially under stress, have tissue specificity.…”
Section: Discussionmentioning
confidence: 63%
“…On the other hand, the role of stress as one of the causes of atherosclerosis, ulcerous lesions of the mucous membrane of the stomach and duodenum, heart and liver function impairment, immunodeficiency and cancer diseases is discussed in numerous studies (Gupta et al, 2012;Cai & Yan, 2013;Gupta et al, 2014;Rabasa & Dickson, 2016). In this regard, the problems of chemical regulation of stress and the search for biologically active substances which have antioxidant activity (AOA) will always be relevant and are the subject of ongoing research by scientists around the world (Khavrona, 2015;Shkurashivska & Erstenyuk, 2015). Despite the large amount of work on the subject, there is a need for additional experimental data to expand our knowledge about the mechanisms of action of antioxidants, especially products of natural origin.…”
Section: Introductionmentioning
confidence: 99%
“…One of the identified effects of chronic social stress is a significant change in the ratio of serum lipoproteins and blood lipid spectrum, choles-terol synthesis and receptor-mediated transport, fatty acid synthesis and oxidation and cholesterol and triglyceride content in liver cells and other lipid disorders (Chuang et al, 2010;Scott et al, 2012;Shkurashivska & Ersteniuk, 2015). The key reactions of cholesterol metabolism take place in the liver.…”
Section: Introductionmentioning
confidence: 99%